ROLES OF BROADCAST MEDIA FOR INSTRUCTIONAL DELIVERY IN OPEN AND DISTANCE LEARNING: NIGERIA AS A CASE STUDY - Adegbija, M.V.; Fakomogbon, M.A.; Adebayo, M.S. (European Scientific Journal, ESJ, 2013)
Broadcast media involve the transmission of information, ideas and opinions through the usage of electronic devices. The Open and Distance Learning (ODL) is becoming more and more relevant and accepted as a form of global education. Radio broadcasting was introduced in Nigeria during the colonial age in 1932. Since then, it has been used for social, political and mass education. This paper examines the roles of broadcast media for educational delivery in ODL using Nigeria as a case study. It further examines the concept of ODL, broadcasting delivered through the usage of information and communication technology tools and the constraints in the use of broadcast media as an ODL educational delivery.